2008
DOI: 10.4049/jimmunol.181.3.1655
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Selective Effect of PA28 in MHC Class I Antigen Processing

Abstract: PA28 is an IFN-γ-inducible proteasome activator and its genetic ablation causes complete loss of processing of certain Ags, but not all of them. The reason why this occurs and how PA28 influences the formation of peptide repertoires for MHC class I molecules remains unknown. In this study, we show the allele-specific role of PA28 in Ag processing. Retrovirus-transduced overexpression of PA28α decreased expression of Kd (Dd) while it increased Kb and Ld on the cell surface. By contrast, overexpression of PA28αΔ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Conversely, a substantial increase of antigenicity was observed in B16F1 KbϪ , while a substantial decrease was seen with the H-2Kb-expressing B16 cells. Similar findings were observed using Pmel-1 TCR-transgenic CD8 T cells specific for the H-2Db-restricted gp100 25 epitope, 20 except that IFN␥ increased the antigenicity of all 3 H-2Kb-loss variants (supplemental Figure 8).…”
Section: Noncognate Mhc-i Levels Reduce the Ability Of Ctl To Recognisupporting
confidence: 79%
See 3 more Smart Citations
“…Conversely, a substantial increase of antigenicity was observed in B16F1 KbϪ , while a substantial decrease was seen with the H-2Kb-expressing B16 cells. Similar findings were observed using Pmel-1 TCR-transgenic CD8 T cells specific for the H-2Db-restricted gp100 25 epitope, 20 except that IFN␥ increased the antigenicity of all 3 H-2Kb-loss variants (supplemental Figure 8).…”
Section: Noncognate Mhc-i Levels Reduce the Ability Of Ctl To Recognisupporting
confidence: 79%
“…All of the cell lines were cultured in medium supplemented with 10% fetal bovine serum, as recommended by the providers. Transfected B16 cells were prepared with SuperFect reagent (QIAGEN) using various cDNA plasmids: a dominant-negative IFN␥R1 24 (IFN␥R DN ) construct (W. Lee, University of Pennsylvania, Philadelphia, PA); a short hairpin RNA (shRNA) construct for the immunoproteasome PA28␣ subunit 25 (H. Udono, RIKEN Yokohama Institute, Yokohama, Japan); a construct encoding a single-chain trimer H-2Kb-␤2M-Ova 257 (scKb Ova ) 26 molecule (J. Connolly, Washington University, St. Louis, MO); and a plasmid encoding the heavy chain of H-2Kb (L. Pease, Mayo Clinic, Rochester, MN). After transfection, stable clones were isolated with a combination of drug selection, flow cytometric sorting, and cell cloning at limiting dilutions.…”
Section: Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding of PSME1 and PSME2 to the i20S has recently been shown to increase the capacity of i-proteasomes to selectively degrade oxidized proteins (44) and accelerate the generation of a subset of MHC class I-presented antigenic peptides (9,45,46). In addition, in situ PLA showed that both PSME1 associated proteasomes and i-proteasomes were mainly localized in the cytosol of C2C12 cells.…”
Section: Discussionmentioning
confidence: 95%